Estudo da interação da piplartina com albumina do soro humano por técnicas espectroscópicas - Contessoto, Nayara Sousa de Alcântara [UNESP] (2017)
Piplartine is an alkaloid amide present in roots and stems of different peppers species of the genus Piper. This compound has several promising pharmacological properties, such as: antidepressant, anxiolytic, genotoxic, cytotoxic, antiangiogenic, antimetastatic, among others; Its anticancer property is highlighted, because this compound does demonstrate greater anti-proliferative effect in altered cells than in normal cells. Studies have determined the pharmacokinetic parameters of piplartine in rat plasma by intraperitoneal administration, however, without pointing any molecular target or describing the physicochemical forces of the interaction. This study was conducted to understand the interaction between piplartine (PPTN) and human serum albumin (HSA), which is the predominant protein in blood plasma and carrier of various drugs. This interaction was investigated through steady-state fluorescence spectroscopy, monitoring the fluorescence emission of the single tryptophan residue of HSA (Trp214). It was observed the complex HSA-piplartine formation. The thermodynamic parameter analysis indicates that the process occurs spontaneously and it is enthalpically driven; the affinity constant suggests that this interaction is reversible. It was indicated by the binding density function method and by the site marker displacement analysis that the piplartine binds on HSA at single site, which was determined like the IIA sub-domain.